2014
DOI: 10.12659/aot.889441
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic adenoma of the urinary bladder: A report of three cases and a review of the literature

Abstract: Although NA is a benign metaplastic lesion of the urothelium, its recurrence rate is relatively high, thus careful and regular follow-up is necessary. Endoscopic characteristics of NA are not specific and a definite diagnosis must be made after histological analysis of resected specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Kuzaka et al [ 46 ] reported 3 cases of nephrogenic adenoma of the urinary bladder which were treated in their hospital between February 2011 and December 2012. They stated that all of the 3 patients had undergone previous open surgery.…”
Section: Results/literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuzaka et al [ 46 ] reported 3 cases of nephrogenic adenoma of the urinary bladder which were treated in their hospital between February 2011 and December 2012. They stated that all of the 3 patients had undergone previous open surgery.…”
Section: Results/literature Reviewmentioning
confidence: 99%
“…The remaining two patients had nephrogenic adenoma of the bladder only. Kuzaka et al [ 46 ] also reported that recurrent nephrogenic adenomas were diagnosed in 2 patients and the time to disease relapse was 5 months and 9 months; all the nephrogenic adenomas and recurrent tumours were treated by means of transurethral resection. …”
Section: Results/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1950, the term ‘nephrogenic adenoma’ (NA) was coined in a case series of patients describing similar pathologic findings in the bladder ( 2 ). Small case series have reported NA occurring concurrently with bladder cancer ( 3 , 4 7 ). Though TCC may be concurrent with the findings of nephrogenic adenoma, malignant transformation of nephrogenic adenoma has only been demonstrated in a few small case series ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though TCC may be concurrent with the findings of nephrogenic adenoma, malignant transformation of nephrogenic adenoma has only been demonstrated in a few small case series ( 8 10 ). The predisposing factors for this lesion are poorly understood, though many studies will report prior trauma or inflammation to play a role in the development of NA such as recurrent urinary tract infections, chronic catheterization or administration of intravesical therapy ( 3 – 5 , 7 , 8 , 10 15 ). Given its rarity, there are very few large series to assess these concerns and no clear guidance on its management and follow-up ( 16 ).…”
Section: Introductionmentioning
confidence: 99%